The Effectiveness of Using Kickboards and Pull Buoys for Aquaphobic Students with Freestyle Swimming Ability - Akbar Yusuf; Ikadarny; Haeril (Journal Physical Health Recreation (JPHR), 2025)
This study aims to determine the effectiveness of kickboard and pull buoy use for students with aquaphobia. It also aims to determine whether kickboard and pull buoy use affects their freestyle swimming ability. The Aquaphobia Scale Questionnaire (ASQ) questionnaire was used to determine the effect of kickboard and pull buoy use on freestyle swimming ability. The research method used was a randomized purposive randomized experimental study (pretest-posttest). A pretest was administered to all 20 STKIP YPUP students enrolled in swimming courses with aquaphobia. These students were divided into two groups using paired ordinal matching. Data analysis used a t-test with a significance level of 0.05. The results of this study indicate a significant difference in the effect of kickboard and pull buoy training groups, with an average of 12.09 at a significance level of 0.25. There was a significant difference in the effect of the kickboard and pull buoy training groups using the Aquaphobia Scale Questionnaire (ASQ) questionnaire, with an average increase of 7.70 at a significance level of 0.25. This indicates excellent effectiveness of using the kickboard, both using the Aquaphobia Scale Questionnaire (ASQ) questionnaire and through direct practice with freestyle swimming skills.